A Case Study on the Energy Estimation of open Source Software Testing Tools - Dr. M Mohankumar, Anithakrishna G (International Journal of Advanced Science and Technology, 2020)
Green software engineering aims to develop eco-friendly software that have minimal or no impact on the environment. In the process of designing and developing green software, responsible software developers should focus on various approaches for minimizing the energy impact of the product on the environment. In this paper, an automated testing tool is validated using a power consumption tool to estimate energy consumption. We conduct an experiment using JMeter and Joule Meter to measure the energy consumption of the application by defining various test plans for the various paths of a website setting different assertions. Here, we calculate the power taken to load a website using JMeter, and the result is displayed. The aim is to minimize the power consumption conforming to the green standard of computing